EP-582 Giant bilateral intrathoracic involvement from pseudomyxoma peritonei. (9th August 2022) - Hunduma, Gabriel; Kukreja, Roy; Veres, Lukacs; Tamburrini, Alessandro
Abstract: A 46 year old male never smoker was referred to the unit for investigation of progressively worsening shortness of breath, 9 months after being treated for pseudomyxoma peritoneum. He had completed 3 cycles of CAPOX chemotherapy followed by total colectomy and hyper-thermic intraperitoneal chemotherapy (HIPEC). Computed tomography showed very extensive and bulky bilateral intrathoracic disease with large infiltrations in the parietal and visceral pleura, pericardium and diaphragm, suggesting significant intrathoracic extension of pseudomyxoma peritoneum. Following MDT discussion, pleurectomy and decortication with cytoreductive intent was performed. A pleural mass measuring 5cm was resected, along with drainage of copious amounts of yellow gelatinous material. Extra-pleural dissection was continued up to the apex from the mediastinum and diaphragm. Pericardial tissue was also resected and reconstructed with a vycril mesh. He was discharged home on postoperative day 6 and found to have significant improvement in his symptoms 3 months after surgery.